2016
DOI: 10.5664/jcsm.6196
|View full text |Cite
|
Sign up to set email alerts
|

Flumazenil for the Treatment of Refractory Hypersomnolence: Clinical Experience with 153 Patients

Abstract: A commentary on this article appears in this issue on page 1321.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…A trial (NCT01183312) utilized retrospective chart review of 153 patients treated with flumazenil transdermal cream and/or sublingual flumazenil titrated up to 12 mg 4×/d 55. The study showed symptomatic reduction in sleepiness in 62.8% of patients, with mean reduction of ESS by 4.7±4.7.…”
Section: New Developments and Future Therapiesmentioning
confidence: 99%
“…A trial (NCT01183312) utilized retrospective chart review of 153 patients treated with flumazenil transdermal cream and/or sublingual flumazenil titrated up to 12 mg 4×/d 55. The study showed symptomatic reduction in sleepiness in 62.8% of patients, with mean reduction of ESS by 4.7±4.7.…”
Section: New Developments and Future Therapiesmentioning
confidence: 99%
“…Although this enhancement of GABAergic transmission has not been shown to be causal to sleepiness or long sleep durations in patients with IH, biological plausibility is demonstrated by the known GABAergic mechanisms of sleep onset and maintenance, as well as the prominent role of GABA-A receptor agonists/modulators in the production of pharmacologic sleep and anesthesia (9–12). Further, symptoms of IH are reversible in some patients with use of GABA-receptor antagonists or negative allosteric modulators (see Treatment Resistance , below) (8, 13, 14). …”
Section: Introductionmentioning
confidence: 99%
“…Flumazenil is a competitive antagonist of benzodiazepines without intrinsic activity upon GABA signaling 1012 , so the most parsimonious explanation for its relieving sleepiness is via reversal of endogenous PAMs of GABA A Rs. 13 Sustained, clinically-significant benefit was observed in ~40% of 153 treatment-refractory hypersomnolent subjects with open-label use of compounded flumazenil. 13 …”
Section: : Clinical Implicationsmentioning
confidence: 99%
“…13 Sustained, clinically-significant benefit was observed in ~40% of 153 treatment-refractory hypersomnolent subjects with open-label use of compounded flumazenil. 13 …”
Section: : Clinical Implicationsmentioning
confidence: 99%